Standards of external fixation in prolonged applications to allow safe conversion to definitive extremity surgery: the Aachen algorithm for acute ex fix conversion. (September 2015) - Horst, Klemens; Andruszkow, Hagen; Weber, Christian; Dienstknecht, Thomas; Hildebrand, Frank; Tarkin, Ivan; Pape, Hans-Christoph
Abstract: External fixation has become an important tool in orthopedic surgery. Technology has improved the design and material as well as the construct of the fixator. As most patients are converted from external fixation to definite stabilization during later clinical course, prevention of complications such as infection is of high importance. Based on the current literature, principles of temporary external fixation were summarized. We focused on minimizing the risk of infection and introduce a standardized algorithm how to proceed when converting from external to internal fixation, which also was examined for effectiveness.